Influence of different doses of locking solution on the incidence of phlebitis and tube blockage caused by mannitol infusion via indwelling needle - TAN, Sina; LI, Li (Chinese Journal of Integrative Nursing, 2022)
Objective To compare the influence of different doses of normal saline as locking solution on incidence of phlebitis and tube blockage caused by mannitol infusion via indwelling needle. Methods According to the order of hospital admission, 52 patients with mannitol infusion via indwelling needle were divided into two groups, 24 cases with hospital admission between September and December 2021 in the control group and 28 cases with hospital admission between January and April 2022 in the study group. The saline solution was used with doses of 5 mL in the control group and with doses of 10 mL in the study group, respectively. The quality indexes associated with indwelling needle and incidences of phlebitis and catheter blockage were compared between two groups. Results Longer indwelling time of indwelling needle and fewer numbers of puncture attempts were observed in the study group compared with those in the control group (P＜0. 05). No case of phlebitis was found in neither groups. The incidence of catheter blockage was 10. 71%(3/28)in the study group, which was lower than 33. 33%(8/24), with a significant difference (P＜0. 05). Conclusion For patients accepting mannitol infusion via indwelling needle, injection of a dose of 10 mL saline solution for locking the catheter may achieve a better outcome in prevention of catheter blockage and prolonging the indwelling time of indwelling needles. (目的 对比不同封管液剂量对经静脉留置针输注甘露醇所致静脉炎和堵管发生率的影响。方法 选取2020年9月—12月医院眼科收治的使用静脉留置针输注甘露醇的24例患者作为对照组, 另选取2021年1—4月使用静脉留置针输注甘露醇的28例患者作为研究组。对照组封管液剂量选择5 mL生理盐水, 研究组封管液剂量选择10 mL生理盐水。对比两组留置针使用质量、静脉炎发生率与堵管发生率。结果 研究组留置针的留置天数高于对照组, 穿刺次数低于对照组, 差异有统计学意义(P＜0. 05)。两组均无静脉炎发生。研究组堵管发生率10. 71%(3/28), 低于对照组33. 33%(8/24), 差异有统计学意义(P＜0. 05)。结论 静脉留置针输注甘露醇过程中使用10 mL生理盐水优势更加明显, 能够在一定程度上预防堵管的发生, 延长静脉留置针的使用时间, 综合使用效果较好。)